Immunofluorescen Study of Trophoblastic Bound Immunolglobuline G in preeclamptic women at term - AL-Watar, Wifaq M.; Al- Mousawy, khalida M.; AL-Omari, wafa R.; ali, warkaa mahmood (Journal of the Faculty of Medicine Baghdad, 2005)
SummaryBackground: The role of humoral immunity in the pathogenesis of PET is well known so that an altered immune response could be the cause of this disease . Objectives: to evaluate the rule ofplacenta _ bound IgG in the pathogenesis of PET. Methods: 31 pregnant women were included in this study delivered by cesarean section at Baghdad Teaching Hospital , 16 of them were diagnosed and treated for PET. while the rest 15 cases were of normal women of using direct immunoflorescnt test, the level of IgG was detected.Result: Tthe study showed a significant higher level of IgG in the placental biopsy of PET cases than those of control group using ttest, (P